Allelopathic effect of Salix spp. on seeds germination and seedling delvelopment of Raphanus sativus L. - Rosa, Joatan Machado da; Mea, Luiz Gustavo Wiles Della; Agostinetto, Lenita; Boff, Mari Inês Carissimi (Revista de Ciências Agroveterinárias, 2013)
The objective of this study was to evaluate the allelopathic effect of green fresh leaves and crushed fresh barks of three willow species on the seed germination and seed development of radish (Raphanus sativus). The experiment was conducted at the Seed Laboratory of the State University of Santa Catarina - UDESC, Centro de Ciências Agroveterinárias - CAV in 2009. Bioassays were carried out in a complete randomized design with four replications. The treatments consisted of pieces of green fresh leaves and bark of Salix x rubens, Salix viminalis and Salix Smithiana, separately distributed on radish seeds in Gerbox boxes. The control treatment consisted of radish seeds and distilled water. The boxes containing the treatments were transferred into a germinator chamber maintained at constant temperature (25°C) and Relative Humidity (70%). At 24-hour intervals, from the second day after the bioassay start, until the tenth day the number of germinated seeds, speed of germination, length, fresh and dry mass of rootlets were evaluated. Data was subjected to variance analysis, mean comparison and analysis of linear contrasts. The radicle length was the only parameter which differed between the treatments. The contrast analyses between the treatments with green leaves and fresh barks of S. viminalis and S. smithiana showed statistical significance in the radicle length and the roots fresh weight, showing negative allelopathic effects on the growth and development of radish roots. Green leaves and fresh bark of Salix rubens, S. smithiana and S. viminalis do not present a negative allelopathic effects on fresh mass, dry mass, germination percentage and speed of germination in radish. The S. rubens fresh bark can reduce the growth of radish radicle whereas the fresh S. viminalis leaves can stimulate the radicle growth.